Ecological values and environmental sustainability in the Kuranding Lake folktale - Hiasa, Fina; Rahayu , Ngudining; Daryanti , Melia Eka; Agustina , Emi; Pangesti, Nesa Riska; Andriani , Yeni Yulia; W.P. , Candra Rahma (BAHASTRA, 2026)
Local beliefs in the myths surrounding Lake Kuranding are relevant to the lake's existence. This study aims to uncover the ecological values ​​embedded in the Lake Kuranding folktale and their implications for environmental sustainability. This study uses an ecocritical approach, focusing on the social phenomena of the Tanjung Beringin Village community, South Bengkulu, regarding the ecological implications of the Lake Kuranding folktale. The ecological dimension of local narratives tends to be underexplored, even though these narratives are related to the construction of awareness in environmental preservation. This research is a major step towards understanding how the local narrative of the Lake Kuranding folktale represents environmental preservation. Data sources come from literature, interviews, and observations. The results indicate that the Lake Kuranding folktale contains ecological values, namely: (1) self-sufficiency and self-awareness, (2) knowledge of land allocation, and (3) preservation of water and soil sources. The implications of these three ecological values ​​provide numerous benefits, such as the preservation of the lake ecosystem and water sources for two sub-districts in South Bengkulu, an abundance of fish resources, and a foundation for food security for the people of South Bengkulu. The mythical aspects of the Kuranding Lake folklore have transformed into ecological values ​​that guide the community in preserving their natural environment. The existence of the Kuranding Lake folklore today is not only relevant to the oral folklore preservation practices of the Serawai ethnic group in South Bengkulu but also has implications for the lake's sustainability and plays a significant role in the social and economic aspects of the community in South Bengkulu.